Intercultural Communication in Islamic Preaching in the Multicultural Society of Kampung Sawah Bekasi - Abdul Hamid; Miftahussa’adah Wardi; Hayatuddin; Deni Rahman; Agus Idwar Jumhadi; Mohammad Shodiq Ahmad (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Kampung Sawah is known as one of the multicultural areas in Indonesia, where religious, cultural, and ethnic diversity coexist harmoniously. In this context, Islamic da'wah serves not only as a means of conveying religious teachings but also as a medium of intercultural communication that demands sensitivity, tolerance, and adaptive communication strategies. This study aims to analyze the practice of intercultural communication in Islamic da'wah in the multicultural community of Kampung Sawah, with an emphasis on the communication patterns of da'wah preachers, the da'wah approaches used, and the responses of cross-cultural and interfaith communities to these da'wah activities. This study uses a qualitative approach with descriptive-analytical methods, because it aims to understand in depth the phenomenon of intercultural communication in the practice of Islamic da'wah in the multicultural community of Kampung Sawah. The qualitative approach was chosen to explore the meaning, values, and socio-cultural dynamics that underlie the da'wah process, both from the perspective of the da'wah preacher and the recipient community. The results show that Islamic da'wah in Kampung Sawah tends to use a cultural and dialogical approach, prioritizing universal values ​​such as tolerance, brotherhood, justice, and peace. The preachers not only convey Islamic messages in a normative manner but also accommodate local wisdom, everyday language, and local traditions. This inclusive communication approach has proven effective in building harmonious social relations and minimizing the potential for interfaith conflict. Thus, intercultural communication in Islamic preaching in Kampung Sawah serves as a model of moderate preaching relevant to Indonesia's multicultural society.